Sacrolide A, a new antimicrobial and cytotoxic oxylipin macrolide from the edible cyanobacterium Aphanothece sacrum - Oku, Naoya; Matsumoto, Miyako; Yonejima, Kohsuke; Tansei, Keijiroh; Igarashi, Yasuhiro (Beilstein Journal of Organic Chemistry, 2014)
Macroscopic gelatinous colonies of freshwater cyanobacterium Aphanothece sacrum, a luxury ingredient for Japanese cuisine, were found to contain a new oxylipin-derived macrolide, sacrolide A (1), as an antimicrobial component. The configuration of two chiral centers in 1 was determined by a combination of chiral anisotropy analysis and conformational analysis of different ring-opened derivatives. Compound 1 inhibited the growth of some species of Gram-positive bacteria, yeast Saccharomyces cerevisiae and fungus Penicillium chrysogenum, and was also cytotoxic to 3Y1 rat fibroblasts. Concern about potential food intoxication caused by accidental massive ingestion of A. sacrum was dispelled by the absence of 1 in commercial products. A manual procedure for degrading 1 in raw colonies was also developed, enabling a convenient on-site detoxification at restaurants or for personal consumption.
Keywords: Aphanothece sacrum; cyanobacterium; food intoxication; natural products; sacrolide A; suizenji-nori

(untitled) - Chlipala, G. E.; Mo, S.; Orjala, J. (Curr. Drug Targets, 2011)

(untitled) - Tan, L. T. (Phytochemistry, 2007)

(untitled) - Bérdy, J. (J. Antibiot., 2012)

(untitled) - Oku, N.; Yonejima, K.; Sugawa, T.; Igarashi, Y. (Biosci., Biotechnol., Biochem., 2014)

(untitled) - Kabata, K.; Okamoto, C.; Sasada, N.; Ono, M.; Igoshi, K.; Kobayashi, K.; Masuoka, C.; Ito, Y. (Proc. Fac. Agric., Kyushu Tokai Univ., 2005)

(untitled) - Kabata, K.; Okamoto, C.; Odahara, T.; Nakazono, T.; Osumi, K.; Sasada, N.; Ichikawa, T.; Kaneko, Y.; Aramaki, S. (Proc. Fac. Agric., Kyushu Tokai Univ., 2007)

Shokuhin Kako Soran - Kabata, K. (Suizenji-nori, 2002)

(untitled) - Uchihira, T.; Naito, S.; Masuoka, C.; Okamoto, C.; Yasuda, S. (Proc. Fac. Agric., Kyushu Tokai Univ., 2013)

Search system of Japanese red data

(untitled) - Watanabe, F.; Miyamoto, E.; Fujita, T.; Tanioka, Y.; Nakano, Y. (Biosci., Biotechnol., Biochem., 2006)

(untitled) - Ngatu, N. R.; Okajima, M. K.; Yokogawa, M.; Hirota, R.; Eitoku, M.; Muzembo, B. A.; Dumavibhat, N.; Takaishi, M.; Sano, S.; Kaneko, T.; Tanaka, T.; Nakamura, H.; et al. (Ann. Allergy, Asthma, Immunol., 2012)

(untitled) - Ödman, P.; Wessjohann, L. A.; Bornscheuer, U. T. (J. Org. Chem., 2005)

(untitled) - Hatch, R. P.; Shringerpure, J.; Weinreb, S. M. (J. Org. Chem., 1978)

(untitled) - Oku, N.; Takada, K.; Fuller, R. W.; Wilson, J. A.; Peach, M. L.; Pannell, L. K.; McMahon, J. B.; Gustafson, K. R. (J. Am. Chem. Soc., 2010)

(untitled) - Trost, B. M.; Belletire, J. L.; Godleski, S.; McDougal, P. G.; Balkovec, J. M.; Baldwin, J. J.; Christy, M. E.; Ponticello, G. S.; Varga, S. L.; Springer, J. P. (J. Org. Chem., 1986)

(untitled) - Andreou, A.; Brodhun, F.; Feussner, I. (Prog. Lipid Res., 2009)

(untitled) - Hayashi, Y.; Ishihara, N.; Takahashi, M.; Fujii, E.; Uenakai, K.; Masada, S.; Ichimoto, I. (Biosci., Biotechnol., Biochem., 1996)

(untitled) - Hayashi, Y.; Nishikawa, Y.; Mori, H.; Matsushita, Y.; Sugamoto, K.; Matsui, T. (Biosci., Biotechnol., Biochem., 1998)

(untitled) - Mueller, M. J.; Berger, S. (Phytochemistry, 2009)

(untitled) - Barros, L. F.; Kanaseki, T.; Sabirov, R.; Morishima, S.; Castro, J.; Bittner, C. X.; Maeno, E.; Ando-Akatsuka, Y.; Okada, Y. (Cell Death Differ., 2003)

(untitled) - Bøe, R.; Gjertsen, B. T.; Vintermyr, O. K.; Houge, G.; Lanotte, M.; Døskeland, S. O. (Exp. Cell Res., 1991)

(untitled) - Oku, N.; Matsunaga, S.; Wada, S.; Watabe, S.; Fusetani, N. (J. Nat. Prod., 2000)